HIV-1 Replication in HIV-Infected Individuals Is Significantly Reduced When Peripheral Blood Mononuclear Cells Are Superinfected with HSV-1 - Taneth Yamsuwan; Chintana Chirathaworn; Pokrath Hansasuta; Parvapan Bhattarakosol (The Scientific World Journal)
Herpes simplex virus (HSV) can cause generalized infection in human immunodeficiency virus- (HIV-) infected patients leading to death. This study investigated HSV-1 replication in PBMCs from 25 HIV-infected individuals and 15 healthy donors and the effects of HSV-1 superinfection on HIV-1 production. Herpes viral entry mediator (HVEM) receptor on T lymphocytes was also evaluated. Our results confirmed that the number of activated (CD3+ and CD38+) T lymphocytes in HIV-infected individuals (46.51±17.54%) was significantly higher than in healthy donors (27.54±14.12%, P value = 0.001) without any significant differences in HVEM expression. Even though the percentages of HSV-1 infected T lymphocytes between HIV-infected individuals (79.25±14.63%) and healthy donors (80.76±7.13%) were not different (P value = 0.922), yet HSV-1 production in HIV-infected individuals (47.34±11.14×103 PFU/ml) was significantly greater than that of healthy donors (34.17±8.48×103 PFU/ml, P value = 0.001). Moreover, HSV-1 virions were released extracellularly rather than being associated with the cells, and superinfection of HSV-1 at a multiplicity of infection (MOI) of 5 significantly decreased HIV production (P value < 0.001).